2014
DOI: 10.1093/tropej/fmu018
|View full text |Cite
|
Sign up to set email alerts
|

Soil-Transmitted Helminthiases in Secondary School Students in Selected Sites in Two Provinces in the Philippines: Policy Implications

Abstract: The latest World Health Organization (WHO) strategic plan for eliminating soil-transmitted helminthiases (STHs) as a public health problem in children puts the emphasis on school-age children. On the other hand, the Philippine national helminth control program excludes secondary school students in mass deworming for STH. This study determined the prevalence and intensity of STH in a sample of 633 students (14-15 years old) in selected secondary schools in two Philippine provinces. Stool specimens were processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 9 publications
2
12
0
Order By: Relevance
“…Results presented here, from the first survey in August 2015, revealed that 27.81% of participants remain infected with at least one STH. Similar STH prevalence were recently recorded in the Philippines [ 19 ], Cambodia [ 20 ] and Vietnam [ 21 ]. The prevalence of each STH in SAC was also higher than the last reported measurements in 2013 [ 13 ], indicating that more comprehensive M&E is required to accurately assess the national burden of STH.…”
Section: Discussionsupporting
confidence: 86%
“…Results presented here, from the first survey in August 2015, revealed that 27.81% of participants remain infected with at least one STH. Similar STH prevalence were recently recorded in the Philippines [ 19 ], Cambodia [ 20 ] and Vietnam [ 21 ]. The prevalence of each STH in SAC was also higher than the last reported measurements in 2013 [ 13 ], indicating that more comprehensive M&E is required to accurately assess the national burden of STH.…”
Section: Discussionsupporting
confidence: 86%
“…However, these data constitute the most up to date information on the prevalence of STH infections in the Philippines. The most recent studies only cover the prevalence of STH infections on a regional level [ 15 , 18 , 24 , 25 ], but provide sufficient evidence to suggest that the national level of prevalence is still similar to that of the 2005–2007 survey. Therefore, we anticipate our survey data is still relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting treatment, prevention and control activities to communities with high-intensity STH infections, or co-infections, could lead to a more efficient reduction in transmission and severe STH-related morbidity compared to targeting treatment based only on prevalence of single infections [ 21 23 ]. Despite intervention schemes being implemented to reduce morbidity attributable to STH infections in the Philippines [ 11 , 17 ], persistently high prevalence rates among school-aged children continue to be recorded across the country [ 15 , 18 , 24 , 25 ]. Available evidence suggests that indicators based on co-infections and infection intensities, which are linked to higher degrees of morbidity, are useful for estimating disease burden.…”
Section: Introductionmentioning
confidence: 99%
“…Faecal samples were collected from individuals and examined by real-time PCR (qPCR) assay 545 All ages qPCR 58.17% - 48.07% ( Ancylostoma spp.) - - Gordon et al, 2015 [ 45 ] 2011–2012 A cross-sectional survey conducted to determine prevalence and intensity of infection in selected secondary schools in two provinces (Cavite and Guimaras) 633 14–15 years old KK 19.7% 21.5% 0.2% 31.3% 7.7% (M–H) Belizario et al, (2014) [ 41 ] 2012 A cross-sectional survey conducted in 18 rural barangays in Northern Samar to determine the prevalence of single and multiple species helminth infections and the underlying risk factors of acquiring one or more parasite species 6976 All ages KK 36.5%, 61.8%, 28.4%, 75.8% - Ross et al, 2017 [ 42 ] 2013 A cross-sectional survey conducted to determine the prevalence and intensity of STH infections and determine the nutritional status of PSAC and SAC in two villages in Southern Leyte that benefitted from CLTS 316 PSAC and SAC KK 15.8% 19.9% 1.2% 27.9% 7.9% (M–H) Belizario et al (2015) [ 32 ] 2013 A cross-sectional survey conducted to determine the status of STH in SAC in Masbate after a decade of implementation of an integrated helminth control programme 1224 PSAC KK …”
Section: Introductionmentioning
confidence: 99%